Stability Limits of Ni-Based Hydrogen Oxidation Electrocatalysts for Anion Exchange Membrane Fuel Cells - Davydova, Elena S.; Speck, Florian; Paul, Michael T. Y.; Dekel, Dario R.; Cherevko, Serhiy (ACS Catalysis, 2019)
Among the non-noble-metal electrocatalysts for the hydrogen oxidation reaction (HOR) in anion exchange membrane fuel cells (AEMFCs), Ni-based nanoparticles have shown the highest reported activities. In this work, we investigated the chemical and electrochemical stability of representative Ni-based electrocatalysts. For this, carbon-supported monometallic Ni and bimetallic Ni3M (M = Co, Fe, Cu, Mo) nanoparticles were synthesized and tested using a set of complementary techniques. It was found that Mo suffers from intense dissolution due to thermodynamic instability. Cu was stable below 0.4 VRHE, though it undergoes noticeable electrochemical transient dissolution if the potential range is extended to 0.5 VRHE and higher. However, Ni, Co, and Fe showed negligible dissolution up to 0.7 VRHE. Despite the absence of dissolution, all catalysts lose their HOR activity if they are cycled to these high potentials. Physicochemical characterization of the aged catalysts revealed full oxidation of the metal nanoparticles, which could be responsible for the performance deterioration. Although our results demonstrate that, besides Ni3Mo, all studied materials show high stability under operating potentials of AEMFCs, if fuel starvation in AEMFCs results in high anodic potentials, cell activation and operation strategies are needed to prevent the passivation of the catalysts. These results present critical insights toward the design and development of affordable Ni-based electrocatalysts for AEMFCs as well as provide a better understanding of the operation strategies for the stability of AEMFCs.
CRIS-Team Scopus Importer:2019-08-30
Keywords: anion exchange membrane fuel cell (AEMFC); electrocatalyst; hydrogen oxidation reaction (HOR); nickel; stability